2021
DOI: 10.18535/ijsrm/v9i05.em01
|View full text |Cite
|
Sign up to set email alerts
|

Loan Recovery Procedures in Tanzania: A Case of Selected Microfinance Institutions in Dar-Es-Salaam, Tanzania

Abstract: The study aimed to determine the procedures employed by MFIs, specifically in loan recovery in Tanzania. Loan recovery has been a difficult task for many financial institutions but becomes more challenging to microfinance institutions due to the nature and processes they employ. The study examined the loan recovery procedures at NFBS, SMF and AML found in Dar-Es-Salaam, Tanzania. The researcher employed a mixed- case study design, which involved 50 credit officer respondents obtained under the purposive sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…As the above context presents, it is overt that loan recovery is a critical aspect for financial institutions, especially microfinance institutions (MFIs), as highlighted by Sikira (2021). In Tanzania, MFIs face unique EM-2024-6098 challenges in loan recovery due to their operational nature, making it imperative for them to establish formal and efficient recovery processes to ensure sustainability and financial viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the above context presents, it is overt that loan recovery is a critical aspect for financial institutions, especially microfinance institutions (MFIs), as highlighted by Sikira (2021). In Tanzania, MFIs face unique EM-2024-6098 challenges in loan recovery due to their operational nature, making it imperative for them to establish formal and efficient recovery processes to ensure sustainability and financial viability.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from Kenya's experience, loan recovery processes in Tanzania pose a significant challenge for microfinance institutions due to the unique characteristics of the market and borrowers. Research has shown that microfinance institutions in Tanzania encounter difficulties in recovering loans, which are further complicated by the methods and processes they utilise (Sikira, 2021). These challenges are exacerbated by factors such as business losses, payment delays from debtors, and issues in managing group members to attend loan centres (Kitomo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%